Assessing Performance Dimensions in Architecture, Engineer-ing and Construction Organizations - Katsanis, Constantine J. (Advances in Social Sciences Research Journal, 2022)
The collaborative nature of the project environment of the Architecture, Engineering and Construction (AEC) industry necessitates close and prolonged collaboration of diverse organizations in order to execute a project. For the duration of the project, a certain degree of strategic alignment amongst the participating organizations often becomes necessary for the successful execution of the project. The impact of such strategic alignments on the organization’s own performance, is often inevitable. While the performance criteria for the project may be clearly defined along with the project’s program and specifications, the performance criteria that each participating organization has set for itself are not always as evident or articulated to others. In this paper, the results of an exploratory field research are presented. The data analysis revealed that both shared and unique dimensions of performance apply to Architecture, Engineering and Construction organizations. The research findings are significant in that they provide a framework for assessing the degree of compatibility, in terms of shared strategic goals, for firms engaging in projects networks and alliances.